СТЕРЕОТИПИЗИРАНИ ПРЕТСТАВИ ЗА ЖЕНАТА ВО МАКЕДОНСКОТО ФРАЗЕОЛОШКО ТВОРЕШТВО (Philological Studies, 2019)
Bearing in mind the correlation between language and the world that surrounds us, the purpose of this paper is to illustrate certain stereotypical representations of the category of woman in the Macedonian traditional community, through an analysis of a corpus of various phraseological units (in a wider sense of the word). We are focusing on her role as wife and her behavior within the frameworks of the ideal and the realistic model of organizing relations in the traditional community. The inert character of the language makes it pliant to the survival and shifting of stereotypes, which have an impact on the shaping of the consciousness of the new generations.
Keywords: Macedonian traditional community, woman, phraseology, ideal model, real model, stereotypes, language